Nocebo Effects and Negative Suggestions in Daily Clinical Practice – Forms, Impact and Approaches to Avoid Them - Hansen, Ernil; Zech, Nina (Frontiers in Pharmacology, 2019)
Doctors not merely observe and describe symptoms and side effects, but influence and even induce them through their communication. In fact, a significant portion of them originate from health care providers via nocebo effects and not from drugs or surgery. Many signals in medical situation perceived by patients have unintentional negative effects by omission of placebo effects, talking in negations, nocebo effects following negative expectations, by negative suggestions and missing therapeutic relationships. Instead, every treatment should be accompanied by words. In addition to information meaning should be expressed. Meaning and positive expectations can also be raised aside from interventions by addressing the basic psychological needs and avoiding known traumatic stressors. A method to neutralize negative expectations is the introduction of alternative possibilities, which reduces the probability of the expected bad outcome. A promising strategy to avoid nocebo effects in informed consent is to always provide risk information together with positive aspects like advantages of the offered therapy, the prophylactic measures to reduce risks, the monitoring for early detection of developing side effects, the prevention of harm by early therapy, and the patient`s own possible contribution to risk reduction. Negative expectations can be recognized by the word “always…” used by a patient when describing complaints. They can be neutralized by verbal mirroring with change of the word “always” to ”often” or “in the past”, thereby shifting focus to exceptions and solutions, and leaving the future undetermined to negative outcome. Apart from inducing expectations, suggestions have inherent effects, especially in medical situations that commonly induce a natural trance state with enhanced attention, self-reference and increased suggestibility. Talking in negations and attempts to neutralize negative words by negation or diminutives achieve the opposite. Many non-verbal suggestions like overhead induction of anesthesia, transport in not indicated strict supine position, and top-down communication add to anxiousness and stress. Further causes of negative effects are misunderstandings, uncertainties, lies, enforcement of passivity and unmatched levels of communication. A major determinant of the harm of negative suggestions or the effectiveness of positive therapeutic communication is the context of the individual patient`s predispositions and of the doctor-patient relationship.